2002
DOI: 10.1046/j.1365-2699.2002.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Three hundred years of forest and land‐use change in Massachusetts, USA

Abstract: Aim The aim of this study was to document changes in forest composition, structure and distribution across Massachusetts, USA, from the time of European settlement (seventeenth century) to the present, and to investigate environmental and historical influences on regional patterns of variation.Location The study area encompasses the State of Massachusetts (69.9-73.5°E, 41.3-42.9°N), a 21,000-km 2 area in the north-eastern United States.Methods A wide range of historical sources was used to document changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
172
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(176 citation statements)
references
References 56 publications
(106 reference statements)
3
172
0
1
Order By: Relevance
“…Using witness tree data in the state of Massachusetts (northeastern United States), Hall et al (38) found that historical land-use change led to an abundance of early successional trees with longlasting legacy effects (39) on forest structure. Also in the eastern Fig.…”
Section: Observing Changes In Plant Communitiesmentioning
confidence: 99%
“…Using witness tree data in the state of Massachusetts (northeastern United States), Hall et al (38) found that historical land-use change led to an abundance of early successional trees with longlasting legacy effects (39) on forest structure. Also in the eastern Fig.…”
Section: Observing Changes In Plant Communitiesmentioning
confidence: 99%
“…The tree species present are the same today as in pre-colonial time, but species' abundances and distributions changed significantly (Table 4 in Fuller et al, 1998;Cogbill et al, 2002;Hall et al, 2002). The species combinations of today's forests differ from those in colonial forests (Foster et al, 1997), reflecting a landscape undergoing continuous human disturbance (Foster, 1992;.…”
Section: Is Puerto Rico's Experience With New Forests Unique?mentioning
confidence: 99%
“…Conservationists should also be aware of the possibility that tree species such as yellow birch and eastern hemlock may be disproportionately important for some species of birds even when these tree species are not dominant components of the vegetation. The potential importance of the diversity and composition of woody plants is particularly important in light of widespread homogenization of tree species composition in eastern deciduous forest because of such factors as fire suppression, intense browsing of tree seedlings by white-tailed deer (Odocoileus virginianus), and the decline of particular species of trees after insect pests and pathogens have been introduced (Abrams 1998, Hall et al 2002.…”
Section: Discussionmentioning
confidence: 99%